Attributes of God in Hadith Narrations of News Attributes - Nizomiddinov Hoshimjon Muhammadjonovich (Genius Publishing Group, 2023)
While researching hadith narrations, it was discovered that Anwar Shah Kashmiri (1875- 1933), known as Allama in hadith, jurisprudence, and other sciences, was a Sunni community member, particularly of the Hanafi sect, and served as its protector. This is especially evident in the narrations about faith and Shariah rulings. In this section, we will look at how Kashmiri interprets narrations about ahkam and faith, as well as his ability to interpret hadiths.
Keywords: Hadith; analysis; commentary; madhhab